Bradykinin-Induced Sensitization of Transient Receptor Potential Channel Melastatin 3 Calcium Responses in Mouse Nociceptive Neurons - Behrendt, Marc; Solinski, Hans Jürgen; Schmelz, Martin; Carr, Richard (Frontiers in Cellular Neuroscience, 2022)
TRPM3 is a calcium-permeable cation channel that is expressed in a range of sensory neurons and can be activated by heat and the endogenous steroid pregnenolone sulfate. In somatosensory nociceptors, both the expression and sensitivity of TRPM3 can be dynamically regulated under inflammatory conditions. Pharmacological inhibition of TRPM3 can alleviate the development of inflammatory heat hyperalgesia and reduce heat responses of co-expressed TRPV1 and TRPA1. However, neither the mechanisms underlying the regulation of TRPM3 expression nor the details regarding its interplay with other ion channels are known. Here, we show that the inflammatory mediator bradykinin (BK) sensitizes TRPM3-mediated calcium responses to pregnenolone sulfate in acutely isolated dorsal root ganglion neurons. The majority of cells that co-expressed TRPM3 and BK receptors (BKRs) also expressed TRPV1, however only a small fraction co-expressed TRPA1. Signaling pathways responsible for sensitization of TRPM3 following BK were characterized using inhibitors of second messenger signaling cascades. Pharmacological blockade of protein kinase C, calcium–calmodulin-dependent protein kinase II and diacylglycerol (DAG) lipase did not affect BK-induced sensitization, but inhibition of DAG kinase did. In addition, release of calcium ions from intracellular stores using thapsigargin to block SERCA also resulted in TRPM3 sensitization. Our results demonstrate that BKR-mediated activation of intracellular signaling pathways comprising DAG kinase and calcium may contribute to TRPM3 sensitization during inflammation.